(untitled) (Global Journal of Medical Research, 2023)
Introduction Haemorrhoids are very common in everyday life While grades I and II haemorrhoids can be managed conservatively grades III and grade IV haemorrhoids require surgery The study was conducted to determine the better surgical modality for patients undergoing haemorrhoidectomy Open vs MIPH based on the immediate and early post operative complications Aim This study is aimed to compare the two surgical modalities to treat haemorrhoids namely Open Conventional haemorrhoidectomy and Minimally Invasive Procedure Haemerrhoid Stapled Haemorrhoidectomy by comparing their immediate and early post-operative complications